The impact of Gift Policy on elite formation and consequences of greater distancing between union leadership and members in NUM - Makau, Ramatsinele Prudence (University of the Witwatersrand, Johannesburg, 2024)
This research was conducted to investigate whether the Gift Policy incentivizes elite formation within the National Union of Mineworkers (NUM) and with what consequences for union leadership and the union’s rank and file members. One method to assessing the essence of the policy is to analyse the logic for its adoption. Was the Gift Policy in its policy construction an intended or unintended consequence of the leadership of the union’s approach to incentivizing members through differential benefits or something else? The research project aligns with Anyebe (2018) that some policies undermine the solidarity for which unions were formed because the formulation and implementation of internal policies, such as gift policies in the case of the NUM, tend to only reflect the values and preferences of leadership members as the policy in question benefits only a select few and not everyone. Employing a semi- structured interview with leaders and members of the National Union of Mineworkers, this inquiry intended to address concerns relating to the essence and significance of the Gift Policy, and the process by which the Gift Policy was developed, the Gift Policy’s influence on working relationships, the Gift Policy’s impact on the creation of positions of authority and whether it influences privilege between the union’s leadership and ordinary union members. The researcher noted a wide diversity of viewpoints on the Gift Policy. Interpretations range from functional incentivization, which entails improving the transport mobility of the union executive members to perform their tasks with reliable transport to issues of elitism and differential power between leadership and rank and file. This study has significant limitations. Firstly, qualitative research is mostly subjective because it relies on researchers to comprehend respondents' own perceptions (Field, 2013). Secondly, this study focuses solely on the Gift Policy within NUM. Consequently, the findings of the study cannot be generalised to other policies within the union or other political organisations. Thirdly, the study’s sampling consisted of 15 participants of whom only four were females and 11 were males. Moreover, only male participants were in leadership positions. To address these limitations, future studies may employ random sampling techniques on a broader sample to address generalizability issues. When using telephone interviews in their study design, researchers should keep these privacy concerns in mind. Therefore, future researchers will be in a better position to perform a comprehensive qualitative study employing theme analysis, ensuring ii trustworthiness, and delivering significant findings if these limitations are considered and these recommendations are followed. Findings from this study serve as a useful guide for the formation and implementation of incentive policies that will make employees at all levels feel valued, included, and equipped with resources to undertake their tasks as well.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Gift Policy; union leadership; Members in NUM; SDG-17: Partnerships for the goals